Pengaruh Disiplin Kerja, Kompensasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Sasana Antik Kabupaten Rembang - Ahmad Khoirul Anwar; Muhammad Tahwin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research explores how work discipline, compensation, and job satisfaction impact employee performance at PT Sasana Antik in Rembang Regency. The researchers used a sample of 62 employees and collected data through questionnaires. Multiple linear regression analysis was used to analyze the data. The results showed that work discipline has a positive but insignificant effect on employee performance, compensation has a significant positive effect on employee performance, and job satisfaction has a positive but insignificant effect on employee performance. The Adjusted R Square value shows that 19.9% of the variation in employee performance can be attributed to the three independent variables, while the remaining 80.1% can be explained by other factors not examined in this study.